Development of Problem Solving E-Modules to Improve Critical Thinking Skills and Learning Outcomes on Human Body Organ System Material - Ita Trisna Prasetyaningrum; Pramudya Dwi Aristya; Bevo Wahono (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to develop a valid, practical, and effective problem-solving-based e-module on the material of the human body organ system. This study uses the Research and Development (R&D) method with the 4D model. The problem-solving-based e-module shows high validity of 91.4%. The developed e-module gets an average percentage of 87.5% with a very practical category in the small class trial and 88.6% in the large class and is declared practical. The e-module developed in the small class gets a learning outcome test and critical thinking skills with an average n-gain score of 0.76 and 0.77 with a high category. In the large class, it gets a learning outcome test and critical thinking skills with an average n-gain score of 0.75 and 0.78 with a high category. Very good criteria are also obtained in filling out the student response questionnaire by producing an average percentage of 87% in the small class and an average percentage of 86% in the large class. Thus, the problem-solving-based e-module on the material of the human body organ system is considered feasible to be used in the learning process.